2018
DOI: 10.1080/17513758.2018.1475018
|View full text |Cite
|
Sign up to set email alerts
|

An SIR pairwise epidemic model with infection age and demography

Abstract: The demography and infection age play an important role in the spread of slowly progressive diseases. To investigate their effects on the disease spreading, we propose a pairwise epidemic model with infection age and demography on dynamic networks. The basic reproduction number of this model is derived. It is proved that there is a disease-free equilibrium which is globally asymptotically stable if the basic reproduction number is less that unity. Besides, sensitivity analysis is performed and shows that incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In many cases, we realize demography and infection age are important factors in the epidemic disease model [9,21]. However, in the literature [10], it found that the most of the researcher ignored the important effect of the spreading age on the spreading process of the rumor.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In many cases, we realize demography and infection age are important factors in the epidemic disease model [9,21]. However, in the literature [10], it found that the most of the researcher ignored the important effect of the spreading age on the spreading process of the rumor.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, these are not consistent with the reality [14,17]. To make the rumor model more accurate and truthful, after investigating the modern epidemic dynamics models and documents [9,14,21], we introduce the risk function instead of the recovery rate, where the recovery rate depend on the spreading age. Numerical simulations are used to verify the accuracy of the model and ensure the model in line with the reality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method give a good approximation in many works, such as in [5] and [6]. In [5] the method was applied to approximate SIRS epidemic model while in [6] it was applied to find the numerical solution of SIR Pairwise Epidemic model. Euler method is a simple scheme, but only works for a small step-size.…”
Section: Introductionmentioning
confidence: 99%